Economic attractiveness of domestic rainwater harvesting in Brazilian cities - Marcelo Castier (2591737) (2023)
Brazil is the fifth largest country by area in the world, with a variety of climates in its territory. This work assesses the economic attractiveness of domestic rainwater harvesting direct feed systems, for the replacement of non-drinking water, in 148 locations of the Brazilian territory considering hourly rainfall data for the 14-year period between 2008 and 2021. The water tariff and consumption data for each location were also considered along with estimated hourly and monthly consumption patterns. With annual operating expenses at 1% of the capital expenditure and an annual discount rate of 8%, the net present value for the 14-year period is positive in only 15 locations, which are among those with the highest water tariffs in the country. The results of these base case simulations discourage the installation of domestic RWH systems in most of the Brazilian locations considered. However, the results also show that, depending on house occupancy, filtration equipment cost, water tariff, and catchment area, outcomes more favorable to the installation of RWH systems are obtained, especially in cities of Brazil’s southern and southeastern regions. Other Information Published in: Discover Water License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s43832-023-00033-1